The study of the entrepreneurial characteristics and traits of the Marymart Mall businessmen - Peñaranda, Brigg G. (1998)
Fifty respondent businessmen with 7 years minimum business experience in Marymart mall located in Valeria St., Iloilo City, were chosen to determine their entrepreneurial characteristics and traits by using questionnaire. Results reveal that the extent of their entrepreneurial characteristics and traits were to a great extent level. The entrepreneurial characteristics and traits of mary mart Mall businessmen was not associated to their type of business and civil status. However, a significant relationship existed between the businessmen characteristics and traits and their ethnic origin, educational attainment and age group. The researcher recommends that the following programs should be undertaken: (1.) Ensure that education is delivered in a way that will nurture those attributes commonly associated with entrepreneurship. (2.) During the formative period of youth, substantial effort should be made to encourage awareness, understanding, knowledge of, insight into, and positive attitudes towards entrepreneurship through the provision of learning, practical work experience, and exposure to the business environment (3.) Simulations of small business for the young during their education so they understand that a career in small business is an attainable objective. (4.) The introduction of contact networks of suppliers and channels through which customers can be found, and in particular, the introduction to the concept of what constitutes a valid business idea. Particular emphasis has been placed upon entrepreneurship awareness among the youth because of the need to affect career aspirations. The potential to include entrepreneurship awareness in educational programs is considerable. These programs maybe offered in elementary schools, high schools, vocational training institutions, universities, and professional organizations. It is the channeling of young people with substantial ambition and capability of self-employment that will guarantee the health and strength of the small enterprise sector in the long term. However, the same general guidelines would apply to encouraging entrepreneurship awareness among the existing adult population.
Research Paper (Research in Business Management). -- Iloilo City : UPV-CM, 1998.